THE EFFECT OF SEAWATER SOAKING ON THE STABILITY CHARACTERISTICS OF ASPHALT CONCRETE MIXTURES IN THE COASTAL REGION OF PAPUA: PENGARUH RENDAMAN AIR LAUT TERHADAP KARAKTERISTIK STABILITAS CAMPURAN BETON ASPAL DI WILAYAH PESISIR PAPUA - Dinda Sekar Selni Prawardani (UKI Press, 2025)
This research analyzes the effect of seawater immersion on the performance of asphalt concrete mixtures, using the